2005
DOI: 10.1038/sj.onc.1209046
|View full text |Cite
|
Sign up to set email alerts
|

SV40 large T antigen targets multiple cellular pathways to elicit cellular transformation

Abstract: DNA tumor viruses such as simian virus 40 (SV40) express dominant acting oncoproteins that exert their effects by associating with key cellular targets and altering the signaling pathways they govern. Thus, tumor viruses have proved to be invaluable aids in identifying proteins that participate in tumorigenesis, and in understanding the molecular basis for the transformed phenotype. The roles played by the SV40-encoded 708 aminoacid large T antigen (T antigen), and 174 amino acid small T antigen (t antigen), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
405
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(435 citation statements)
references
References 140 publications
11
405
0
1
Order By: Relevance
“…These cells are deficient for both Rb/TP53 activity (due to SV40LT expression [27]) and ASMase (due to targeted insertion of neomycin expressing cassette into the gene [28]), the changes affecting both known vesiculation pathways of exosomal and ectosomal biogenesis, respectively [24,26]. Analysis of this unique panel of cell lines revealed the emission of EVs containing oncogenic N-ras and SV40LT sequences, suggesting EV biogenesis may be independent of the two pathways (Fig.…”
Section: Dna-containing Extracellular Vesicles Are Generated Independmentioning
confidence: 93%
“…These cells are deficient for both Rb/TP53 activity (due to SV40LT expression [27]) and ASMase (due to targeted insertion of neomycin expressing cassette into the gene [28]), the changes affecting both known vesiculation pathways of exosomal and ectosomal biogenesis, respectively [24,26]. Analysis of this unique panel of cell lines revealed the emission of EVs containing oncogenic N-ras and SV40LT sequences, suggesting EV biogenesis may be independent of the two pathways (Fig.…”
Section: Dna-containing Extracellular Vesicles Are Generated Independmentioning
confidence: 93%
“…These observations suggest that SV40 large T plays an essential role in reprogramming sheep somatic cells. SV40 large T is an essential protein for SV40 DNA replication and disables the retinoblastoma and p53 tumor suppressor pathways [31][32][33][34]. It has been reported that knocking down p53 greatly increases reprogramming efficiency [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Sequestration of tumor suppressor proteins by viral oncoproteins is a mechanism commonly employed by oncogenic viruses (Ahuja et al, 2005;O'Shea, 2005;Weitzman and Ornelles, 2005;Felsani et al, 2006). The adenoviral oncoproteins E1A and E1B55K cooperate to transform primary cells in culture (Endter and Dobner, 2004).…”
Section: Introductionmentioning
confidence: 99%